A simple method of short‐term mechanical reliability prediction for ceramics in reactive environments. Issue 7 (13th March 2018) - Cook, Robert F.
Abstract: A method is demonstrated for prediction of ceramic reliability limited by fracture in reactive environments. The simplicity of the method relies on the ceramic displaying ideal indentation‐strength behavior and on the applied loading leading to short‐term power‐law crack velocity behavior. Reactive failure strength measurements, treating flaw size as a variable and failure time as a constraint in a "pass‐fail" test, enable reliability, including both intrinsic and contact flaws, to be predicted. Little to no computation is required.